PENGGUNAAN CAMPURAN BAKTERI ASAM LAKTAT DAN KHAMIR SEBAGAI FLAVOURING AGENT PADA SARI BUAH MENGKUDU TERFERMENTASI THE USE OF LACTIC ACID BACTERIA AND YEASTS COMBINATION AS FLAVOURING AGENT IN FERMENTED NONI JUICE - Handayan, Isti; , Mustaufik (Pembangunan Pedesaan, 2006)
Fermentation in this research was aimed to reduce, remove or recover unpleasant smell and taste of noni juice. The treatment factors were combination of lactic acid bacteria and yeasts, consisting of Lactobacillus acidophillus: Saccharomyces cerevisiae (K1), L. acidophillus: Kluyveromyces marxianus (K2), L. casei: S. cerevisiae (K3) and L. casei: K. marxianus (K4), with fermentation times of 0, 3, 5, and 7 days. The result of this research were: different combination of lactic acid bacteria and yeasts caused significantly decreased of pH and increased of alcohol content, but not significant on the vitamin C content. The biggest decreased on the pH resulted from L. casei: K. marxianus (K4), on the other hand the biggest increased on the alcohol content resulted from L. acidophilus: K marxianus (K2). During fermentation, decrease of pH, vitamin C content and increase on the alcohol content were significant, resulted in the 0 and 3 days of fermentation. The counts of lactic acid bacteria and yeasts increased during 3 days fermentation but after this reduction. Sensory test showed that combination of lactic acid bacteria and yeasts and fermentation times were significant to the odor, flavour, taste and preference. Combination of L. acidophilus: K marxianus (K2) with 5 days fermentation resulted in the best of the noni juice preference.